Investigation of the H tau tau and Hbb coupling constants for a scalar (Pseudoscalar) higgs Boson at a future linear electron-positron collider - Braguta, V. V.; Likhoded, A. A.; Chalov, A. E.; Rosenfeld, Rogério [UNESP] (Maik Nauka/interperiodica Publ, 2004)
The possibility of setting constraints on the Couplings of a scalar (pseudoscalar) Higgs boson to the tau lepton and the b quark in the reactions e(+)e(-)-->v (v) over bar tau(+)tau(-) and e(+)e(-)-->v (v) over barb (b) over bar at a future linear electron-positron collider of total energy roots = 500 GeV is studied. The admixture of a new hypothetical pseudoscalar state of the Higgs boson in the Hf (f) over bar vertex is parametrized in the form (mf/v)(a+igamma(5)b). on the basis of an analysis of differential distributions for the processes under study, it is shown that data from the future linear collider TESLA will make it possible to constrain the parameters a and b as -0.32 less than or equal to Deltaa less than or equal to 0.24 and -0.73 less than or equal to b less than or equal to 0.73 in the case of the reaction e(+)e(-)-->v (v) over bar tau(+)tau(-) and as -0.026 less than or equal to Deltaa less than or equal to 0.027 and -0.23 less than or equal to b less than or equal to 0.23 in the case of the reaction e(+)e(-) --> v (v) over barb (b) over bar. It is emphasized that the contribution of the fusion Subprocess WW --> H in the channel involving an electron neutrino is of particular importance, since this contribution enhances the sensitivity of data to the parameters being analyzed. (C) 2004 MAIK Nauka/Inierperiodica.